2017
DOI: 10.1182/blood-2017-02-767921
|View full text |Cite
|
Sign up to set email alerts
|

Signal integration at the PI3K-p85-XBP1 hub endows coagulation protease activated protein C with insulin-like function

Abstract: Coagulation proteases have increasingly recognized functions beyond hemostasis and thrombosis. Disruption of activated protein C (aPC) or insulin signaling both impair function of podocytes and ultimately cause dysfunction of the glomerular filtration barrier and diabetic kidney disease (DKD). We here show that insulin and aPC converge on a common spliced-X-box binding protein-1 (sXBP1) signaling pathway to maintain endoplasmic reticulum (ER)-homeostasis. Analogous to insulin, physiological levels of aPC maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…found that impaired insulin signalling together with hyperglycemia prevents the nuclear translocation of transcription factor spliced X‐box binding protein 1 (sXBP1), which resulted in maladaptive ER stress signalling in podocytes and worsened DKD. Concomitantly, the same team found that coagulation protease activated protein C (aPC) maintains ER homoeostasis via sXBP1 in podocytes . Specifically, they revealed that aPC can compensate for the absence of insulin receptor in podocytes in mice with experimental diabetes.…”
Section: Diabetes and Diabetic Kidney Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…found that impaired insulin signalling together with hyperglycemia prevents the nuclear translocation of transcription factor spliced X‐box binding protein 1 (sXBP1), which resulted in maladaptive ER stress signalling in podocytes and worsened DKD. Concomitantly, the same team found that coagulation protease activated protein C (aPC) maintains ER homoeostasis via sXBP1 in podocytes . Specifically, they revealed that aPC can compensate for the absence of insulin receptor in podocytes in mice with experimental diabetes.…”
Section: Diabetes and Diabetic Kidney Diseasementioning
confidence: 94%
“…Specifically, they revealed that aPC can compensate for the absence of insulin receptor in podocytes in mice with experimental diabetes. This occurred by activation of the PI3K p85‐subunit‐dependent nuclear translocation of sXBP1, which prevented the maladaptive ER stress …”
Section: Diabetes and Diabetic Kidney Diseasementioning
confidence: 99%
“…62 Experimental studies over the last decade in multiple mouse models of chronic-diabetic and acute kidney injury models delineated multiple cell-specific intracellular mechanisms that mediate aPC-dependent cytoprotective effects. [65][66][67][68] We recently uncovered an insulinlike function of aPC in the regulation of adaptive unfolded protein response in insulin-sensitive specialized glomerular epithelial cells called podocytes. 67 Disruption of aPC or insulin signalling or both impair function of podocytes ultimately causing dysfunction of the glomerular filtration barrier and dNP.…”
Section: Coagulation Protease Signalling In Diabetic Kidney Diseasementioning
confidence: 99%
“…[65][66][67][68] We recently uncovered an insulinlike function of aPC in the regulation of adaptive unfolded protein response in insulin-sensitive specialized glomerular epithelial cells called podocytes. 67 Disruption of aPC or insulin signalling or both impair function of podocytes ultimately causing dysfunction of the glomerular filtration barrier and dNP. 67,69 Mechanistically, insulin and aPC converge on a common spliced-X-box binding protein-1 (sXBP1) signalling pathway to maintain endoplasmic reticulum (ER) proteostasis.…”
Section: Coagulation Protease Signalling In Diabetic Kidney Diseasementioning
confidence: 99%
“…This effect, which conveys protective aspects of ER‐signaling, is lost in insulin resistance, promoting diabetic nephropathy. Activated protein C (aPC) signaling (4) via protease activated receptors 1 and 3 (PAR1/3) restores sXBP1‐p85 dissociation (2) and sXBP1nuclear translocation (3), maintaining kidney function . In vivo, aPC restores ER‐function and protects mice lacking the insulin receptor from aggravated diabetic nephropathy.…”
Section: Cross‐talk Of Insulin and Apc Signaling In The Kidneymentioning
confidence: 99%